Interplay between the lung microbiome and lung cancer. (28th February 2018) - Mao, Qixing; Jiang, Feng; Yin, Rong; Wang, Jie; Xia, Wenjie; Dong, Gaochao; Ma, Weidong; Yang, Yao; Xu, Lin; Hu, Jianzhong
Abstract: The human microbiome confers benefits or disease susceptibility to the human body through multiple pathways. Disruption of the symbiotic balance of the human microbiome is commonly found in systematic diseases such as diabetes, obesity, and chronic gastric diseases. Emerging evidence has suggested that dysbiosis of the microbiota may also play vital roles in carcinogenesis at multiple levels, e.g., by affecting metabolic, inflammatory, or immune pathways. Although the impact of the gut microbiome on the digestive cancer has been widely explored, few studies have investigated the interplay between the microbiome and lung cancer. Some recent studies have shown that certain microbes and microbiota dysbiosis are correlated with development of lung cancer. In this mini-review, we briefly summarize current research findings describing the relationship between the lung microbiome and lung cancer. We further discuss the potential mechanisms through which the lung microbiome may play a role in lung carcinogenesis and impact lung cancer treatment. A better knowledge of the interplay between the lung microbiome and lung cancer may promote the development of innovative strategies for early prevention and personalized treatment in lung cancer. Highlights: The Lungs are not sterile, and the lung microbiome is associated with lung health. The lung microbiome is linked to lung cancer. Microbial dysbiosis may modulate the risk of malignancy at multiple levels.